Can and Should Language Models Act Politically? Hannah Arendt's Theory of Action in Comparison with Generative AI. - OHLY, LUKAS (Filozofia, 2024)
At the heart of the debate about generative or autonomous AI is the concern that it could take action away from humans. Hannah Arendt, who gave the concept of action a political profile and opposed the automation tendencies of modernity, provides a basis for assessing fears that humans will cede their political action to AI. After an introduction to Arendt's political theory of action, the paper examines whether AI can and should act. The focus is on linguistic models.